2007
DOI: 10.1534/genetics.107.077982
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sse1 in the de Novo Formation and Variant Determination of the [PSI+] Prion

Abstract: Yeast prions are a group of non-Mendelian genetic elements transmitted as altered and self-propagating conformations. Extensive studies in the last decade have provided valuable information on the mechanisms responsible for yeast prion propagation. How yeast prions are formed de novo and what cellular factors are required for determining prion ''strains'' or variants-a single polypeptide capable of existing in multiple conformations to result in distinct heritable phenotypes-continue to defy our understanding.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
82
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(91 citation statements)
references
References 48 publications
8
82
1
Order By: Relevance
“…Second, strains with impaired Hsp104 or Hsp70 activity are defective in the generation of new propagons (Ness et al, 2002;Song et al, 2005), whereas NatA mutants sustain wild-type propagon levels (Supplemental Figure S6). Third, the steady-state size of SDS-resistant Sup35 aggregates increases in [PSI ϩ ] strains deficient in Hsp104, Hsp70, or Hsp70 cochaperones (Eaglestone et al, 2000;Wegrzyn et al, 2001;Cox et al, 2003;Kryndushkin et al, 2003;Jones et al, 2004;Song et al, 2005;Fan et al, 2007;Kryndushkin and Wickner, 2007;SatputeKrishnan et al, 2007;Sadlish et al, 2008), an observation that is completely opposed to our findings for NatA mutants ( Figure 5C). In addition to these factors, the ubiquitin-conjugating enzyme Ubc4 and the Hsp70 family members Ssb1 and Ssb2 are predicted or proven substrates for NatA (Huang et al, 1987;Polevoda et al, 1999), are modifiers of the [PSI ϩ ] prion cycle Allen et al, 2007), and have demonstrated synthetic interactions with NatA (Gautschi et al, 2003;Pan et al, 2006).…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…Second, strains with impaired Hsp104 or Hsp70 activity are defective in the generation of new propagons (Ness et al, 2002;Song et al, 2005), whereas NatA mutants sustain wild-type propagon levels (Supplemental Figure S6). Third, the steady-state size of SDS-resistant Sup35 aggregates increases in [PSI ϩ ] strains deficient in Hsp104, Hsp70, or Hsp70 cochaperones (Eaglestone et al, 2000;Wegrzyn et al, 2001;Cox et al, 2003;Kryndushkin et al, 2003;Jones et al, 2004;Song et al, 2005;Fan et al, 2007;Kryndushkin and Wickner, 2007;SatputeKrishnan et al, 2007;Sadlish et al, 2008), an observation that is completely opposed to our findings for NatA mutants ( Figure 5C). In addition to these factors, the ubiquitin-conjugating enzyme Ubc4 and the Hsp70 family members Ssb1 and Ssb2 are predicted or proven substrates for NatA (Huang et al, 1987;Polevoda et al, 1999), are modifiers of the [PSI ϩ ] prion cycle Allen et al, 2007), and have demonstrated synthetic interactions with NatA (Gautschi et al, 2003;Pan et al, 2006).…”
Section: Discussioncontrasting
confidence: 97%
“…Other possible targets include Hsp104, Hsp70, and cochaperones that modulate the ATPase activity of Hsp70. Mutations in all of these factors produce a similar reversion of the [PSI ϩ ] phenotype (Chernoff et al, 1995;Jones and Masison, 2003;Fan et al, 2007;Kryndushkin and Wickner, 2007;Sadlish et al, 2008), but several lines of evidence suggest that these proteins are not the crucial target(s) of NatA. First, our expression profiling, genetic, and biochemical analyses indicate that Hsp104 and Hsp70 are neither the direct nor indirect targets of this pathway (Supplemental Figure S4 and Figure 4, B and C).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Crude protein extracts prepared from C. elegans expressing MoPrP(23-231)-CFP, MoPrP (Q167R)(23-231)-CFP, and MoPrP(23-231)-CFP and MoPrP(Q167R)(23-231)-YFP were treated with the Sarkosyl sample buffer (50 mM Tris-HCl (pH 6.8), 5% glycerol, 2% Sarkosyl, and 0.05% bromophenol blue) at room temperature for 7 min and separated on 1.5% agarose gels supplemented with 0.1% SDS as described [12]. After transferring to a polyvinylidene difluoride membrane (Millipore), membranes were probed with anti-PrP antibody (3F4) and detected with ECL kit (Amersham).…”
Section: Semi-denaturing Agarose Gel Electrophoresismentioning
confidence: 99%
“…Functionally, Sse1 and Fes1 have both been shown to be involved in prion formation and curing, because Sse1 is required for [PSIϩ] propagation, and deletion of either SSE1 or FES1 blocks [URE3] propagation (35,36). Sse1 has been implicated in Hsp70-mediated protein folding at the ribosome, Hsp90 chaperoning of signal transduction, and post-translational translocation of pre-pro ␣-factor (21,22,37,38).…”
mentioning
confidence: 99%